Silk fibroin structural material and multilayer bonding method thereof
By forming and freezing the silk fibroin gel film on the PET substrate, and then performing hot roll compression bonding and compression, the complex design of the internal structure of the silk fibroin block material and the porous membrane bonding problem is solved, and silk fibroin is realized The efficient multi-layer bonding and gradient structural design of structural materials improves its mechanical properties and degradation control in biomedical applications.
Patent Information
- Application Number
- CN202411423213.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-14
Smart Images

Figure CN119303170A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of implant medical materials, and in particular relates to a silk fibroin structural material and a multi-layer bonding method thereof. Background Art
[0002] Multilayer composite biomaterials are expected to address key challenges facing implantable materials, such as providing support strength, controlling drug release, and providing antimicrobial protection, due to their biocompatibility, multifunctionality, and designability of their tissue interfaces. Such multilayer composite materials can be engineered to improve cell adhesion and deliver therapeutic drugs, and can combine materials with different mechanical properties or improve the mechanical properties of single component materials, making them suitable for applications such as in vivo scaffolds (such as orthopedic implants). However, the effective application of multilayer composite materials also faces several key challenges, such as the need to use biocompatible and low-immunogenic raw materials to reduce rejection reactions; the need to regulate degradation rates to control the service life after implantation; the need to achieve strong interlayer adhesion and address manufacturing complexity that hinders large-scale production.
[0003] Silk fibroin has excellent biocompatibility, controllable biodegradability, excellent mechanical properties and low immune response. In the clinical trials of silk fibroin products, its application is concentrated in wound repair dressings (NCT01993030, NCT02091076), orthopedic repair materials (NCT00490594, NCT02205645), inguinal hernia (NCT02487628), surgical sutures (NCT02653924), etc. The applied structural forms include mainly thin films and scaffold materials, but its multi-scale structural materials have broad clinical application prospects. At present, many advances have been made in the preparation of silk fibroin structural materials. For example, amorphous silk fibroin powder is hot-pressed to prepare silk fibroin blocks, and orthopedic screws are prepared by combining subtractive technology (Nat. Mater. 19, 102-108 (2020); Adv. Mater. 36, e2308748 (2024)), layered silk fibroin aerogels are prepared by bidirectional freeze-drying, and silk fibroin monomers are prepared by densification and compression to imitate shell nacreous layer structural materials (Sci. Adv. 8, eabo0946 (2022)), or silk fibroin block materials are prepared by traditional liquid solvent evaporation and solidification method (Nat. Commun. 5, 3385 (2014)). These dense blocks have advantages in supporting orthopedic implants, but they also have shortcomings in specific scenarios such as cell proliferation, tissue integration, material exchange, and mechanical property matching. Therefore, to fully realize their potential in biomedical applications, the preparation of silk fibroin structural materials still needs to overcome the complex design capabilities of improving the internal microstructure of the material and the ability to mass produce.
[0004] The layer-by-layer composite preparation method is an effective strategy to solve this problem. However, due to the uneven surface roughness of the macroscopic silk fibroin film and the lack of sufficient intermolecular interactions in the highly crystalline film, there has been no precedent for achieving multilayer bonding without adding additional additives (such as hydrophilic ions). Summary of the invention
[0005] In order to solve the problems existing in the background technology, namely, the existing silk fibroin block materials have a dense internal structure and lack the ability to design complex internal microstructures of the materials; and the porous silk fibroin film is difficult to dry bond in the absence of an auxiliary agent or an amorphous adhesion layer, the purpose of the present invention is to propose a silk fibroin structural material and a multilayer bonding method thereof.
[0006] The technical solution adopted by the present invention is as follows, comprising the following steps:
[0007] Step S1, firstly, adding a halide salt into formic acid to dissolve it, and after the dissolution is completed, a halide salt-formic acid solution is obtained;
[0008] Step S2, taking degummed silk and dissolving it in the halide-formic acid solution, and placing it in an ultrasonic cleaning machine for shaking, and obtaining a regenerated silk fibroin solution after shaking;
[0009] Step S3, taking a clean PET (polyethylene terephthalate) substrate, using a four-sided preparation device to scrape and coat the regenerated silk fibroin solution on the PET substrate, curing the regenerated silk fibroin solution at room temperature to form a silk fibroin gel film, and drying the silk fibroin gel film;
[0010] Step S4, soaking the dried silk fibroin gel film in water for a preset time, and then placing the PET substrate with the silk fibroin gel film attached thereto into a vacuum freeze dryer for freeze drying to obtain a porous silk fibroin film;
[0011] Step S5, peeling off the porous silk fibroin film obtained after freeze-drying from the PET substrate by mechanical stripping, and hot roller bonding and compression of the peeled layers of porous silk fibroin film in turn to obtain a multi-layer bonded silk fibroin structural material.
[0012] The mass concentration of the halide salt-formic acid solution obtained in step S1 is 0.5-8.7wt%; the halide salt in step S1 includes one of lithium chloride, lithium bromide and calcium chloride.
[0013] In the step S2, the mass ratio of the degummed silk in the halide-formic acid solution is 8-15 wt %.
[0014] In step S4, the specific steps of freeze-drying the silk fibroin gel film are as follows: the silk fibroin gel film is frozen at a vacuum degree of 0.05 to 0.1 MPa and a cold trap temperature of -60 to -50°C, so that the surface of the silk fibroin gel film spontaneously nucleates and freezes, and then freeze-drying is performed in situ to obtain a porous silk fibroin film after freeze-drying.
[0015] In step S4, the film thickness of the porous silk fibroin film is 60 μm to 120 μm, the pore size of the porous silk fibroin film is 200 nm to 5 um, and infrared spectroscopy analysis shows that the surface of the prepared porous silk fibroin film contains 50% to 70% amorphous structural components.
[0016] In the step S5, the multi-layer porous silk fibroin film is hot-rolled bonded at a temperature of 100°C to 200°C, and then the porous silk fibroin film treated with hot-rolling bonding is placed in a constant temperature and humidity chamber with a humidity of 80% to 85% RH for 2 to 3 hours, and finally the porous silk fibroin film is compressed along the thickness direction at a pressure of 5MPa to 6MPa to finally obtain a multi-layer bonded silk fibroin structural material.
[0017] In the step S5, the thickness of the finally obtained multi-layer bonded silk fibroin structural material is greater than 0.1 mm.
[0018] The regenerated silk fibroin solution is added with a graphene oxide aqueous solution with a concentration of 100 mg / g to 200 mg / g.
[0019] A silk fibroin structural material is prepared by adopting the above preparation method.
[0020] The application of the silk fibroin structural material in preparing scaffold materials.
[0021] The silk fibroin structural material contains silk fibroin, and the silk fibroin structural material is made of a porous film containing silk fibroin by a layer-by-layer bonding method; the bonding method is dry hot roller bonding. The porous silk fibroin film is made of a silk fibroin hydrogel film after freeze-drying. The multi-layer bonding method does not require any additional auxiliary agents or adhesives. Auxiliary agents such as hydrophilic ions and other reagents that activate protein viscosity, and adhesives such as glue composed of organic molecules or polymer materials. The hot pressing temperature used in the multi-layer bonding method is 100-200° C. The silk fibroin structural material can soften in a high humidity environment.
[0022] After the silk fibroin structural material softens in a high humidity environment, it can be further pressed to make it dense. Different pressures can lead to different degrees of densification, which can be used to prepare gradient structures. The degradation rate of the gradient structure under enzymatic degradation is also different. After the silk fibroin structural material softens in a high humidity environment, it can also be processed into a three-dimensional plate shape.
[0023] The present invention freeze-dries a gel film containing silk fibroin to prepare a porous silk fibroin film with a honeycomb pore structure. Since the freeze-drying process can keep a relatively high amorphous component (>50%) of the silk fibroin film, two layers of porous silk fibroin films can be dry-bonded under hot rolling conditions without any additional additives or adhesion layers.
[0024] Because the gel film is directly freeze-dried to obtain a porous silk fibroin film with a honeycomb-shaped pore structure, when the silk fibroin block obtained after lamination is softened and densified, under the support of the honeycomb holes, the edge hole structure is the first to collapse and absorb energy. Therefore, different densification pressures can also be used to prepare a silk fibroin block material with a gradient structure, indicating that the present invention can carry out a complicated gradient design for internal microstructures. In addition, the softened silk fibroin board can also be processed into a plate shape under the action of a three-dimensional mold, so that it can be personalized according to the contact interface characteristics of biological tissues.
[0025] The beneficial effects of the present invention are:
[0026] 1. The present invention can bond silk fibroin films layer by layer without any auxiliary agents and adhesives. The silk fibroin film manufacturing process has excellent repeatability, and the obtained silk fibroin block can be controlled to form a gradient structure during the densification process after softening, thereby regulating its degradation rate.
[0027] 2. The densified silk block (silk fibroin structural material) prepared by the present invention also has excellent mechanical properties. Thanks to its hierarchical structure characteristics of micrometer and nanometer scale coordination, its bending strength can reach 130MPa, bending modulus can reach 5.7GPa, and impact strength can reach 10kJ m -2 The silk fibroin board can also be further processed into a board shape according to the structural characteristics of the biological interface. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The embodiments are shown and explained with reference to the drawings. These drawings are used to explain the basic principles and thus only show the aspects that are necessary for understanding the basic principles.
[0029] Figure 1 It is a schematic diagram of the layer-by-layer bonding and densification process of silk fibroin film;
[0030] Figure 2: is a test diagram of the multi-layer composite silk fibroin structural material and the interface adhesion ability, wherein a is a digital photo of the multi-layer composite silk fibroin structural material; b is a digital photo of the peeling test of the silk fibroin film after hot roller bonding; c is a test curve of adhesion energy during the extension of the peeling crack;
[0031] Figure 3 is a picture of the densified silk protein structural material, wherein a is a cross-sectional micrograph of the silk protein structural material after densification under 5MPa pressure, showing a gradient structure in the thickness direction; b is an electron micrograph of the core layer of the silk protein structural material, showing a layered structure and a porous structure; c is an electron micrograph of the shell layer of the silk protein structural material, showing a dense structure; d is a digital photo of the silk protein structural material after enzymatic degradation for six months;
[0032] Figure 4 is a single-edge notch beam test diagram of the densified silk fibroin structural material, wherein a is a cross-sectional digital photo of the single-edge notch beam test specimen; b is the crack initiation toughness (K) of the samples of Example 1-Example 2 and Comparative Example 1-Comparative Example 2. Ic ) and stable crack growth toughness (K Jc ) test results; c is the crack resistance curves of the samples of Example 1-Example 2 and Comparative Example 1-Comparative Example 2;
[0033] Figure 5 It is a schematic diagram of the three-dimensional structural preparation process of multi-layer composite silk protein structural materials;
[0034] Figure 6 It is a three-dimensional structured silk protein structure material diagram, where a is a digital photo of the hemispherical silk protein structure material; b is a digital photo of the three-dimensional structure mechanical compression test process; c is an electron micrograph of the cross-sectional characteristics of the sample after fracture; d is a mechanical compression curve diagram of the three-dimensional structure;
[0035] Figure 7 It is a picture of a three-dimensional structured dense silk fibroin sheet formed by a liquid phase method, wherein a is a digital photo of the hemispherical dense silk fibroin sheet; b is a digital photo of the three-dimensional structure mechanical compression test process; c is an electron micrograph of the cross-sectional characteristics of the specimen after fracture; d is the mechanical compression curve of the three-dimensional structure.
[0036] Figure 8 It is the mechanical compression curve of natural shells. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0038] Example 1
[0039] Step S1, firstly, 0.48 g of calcium chloride is added into 7.8 ml of formic acid to dissolve, and after the dissolution is completed, a calcium chloride-formic acid solution with a concentration of 4.8 wt % is obtained;
[0040] Step S2, taking 1.3 g of degummed silk and dissolving it in the above 6.8 ml of calcium chloride-formic acid solution, and placing it in an ultrasonic cleaning machine for oscillation for 1 hour, and obtaining a regenerated silk fibroin solution after oscillation;
[0041] Step S3, taking a clean PET (polyethylene terephthalate) substrate, using a four-sided preparation device with a thickness of 400 μm to scrape and coat the regenerated silk fibroin solution on the PET substrate, curing the regenerated silk fibroin solution at room temperature to form a silk fibroin gel film, and drying the silk fibroin gel film;
[0042] Step S4, soaking the dried silk fibroin gel film in water for 10 minutes, and then placing the PET substrate with the silk fibroin gel film attached thereto in a vacuum freeze dryer for freeze drying, so that the silk fibroin gel film is frozen at a vacuum degree of 0.05 MPa and a cold trap temperature of -50°C, so that the surface of the silk fibroin gel film is spontaneously nucleated and frozen, and then freeze-dried in situ to obtain a porous silk fibroin film after freeze drying;
[0043] Step S5, peeling off the freeze-dried porous silk fibroin film from the PET substrate by mechanical peeling; the film thickness of the peeled porous silk fibroin film is about 120 μm, the pore size of the porous silk fibroin film is 200 nm to 5 μm, and the amorphous structure component contained in the surface of the prepared porous silk fibroin film is 50% to 70% according to infrared spectroscopy analysis.
[0044] Step S6, bonding and compressing the peeled off multi-layer porous silk fibroin film in sequence by hot roller pressing, so as to obtain a multi-layer bonded silk fibroin structural material.
[0045] Step S6.1, firstly, hot rolling bonding is performed on two layers of porous silk fibroin films at a temperature of 100° C. to 200° C. to obtain a new porous silk fibroin film;
[0046] Step S6.2, repeating step S6.1 multiple times to achieve hot roller bonding of the multi-layer porous silk fibroin film to obtain a silk fibroin block;
[0047] Step S6.3, then place the silk fibroin block that has been treated with hot roller bonding in a constant temperature and humidity chamber with a humidity of 85% RH for 2 hours, and finally compress the silk fibroin block along the thickness direction at a pressure of 5 MPa to finally obtain a multi-layer bonded silk fibroin structural material.
[0048] like Figure 1 As shown, step S6.1 is specifically as follows: placing the two prepared porous silk fibroin films opposite to each other, and bonding them by hot roller pressing at a temperature of 200°C. Since the amorphous components on the surface of the porous silk fibroin film are activated under the action of hot pressing, hydrogen bonds and other bonding effects are promoted to form on the surfaces of the two porous silk fibroin films.
[0049] Through the above method, several to dozens of layers or even more porous silk fibroin films can be composited layer by layer without any additional auxiliary agents and adhesive additives, and the thickness of the prepared silk fibroin block is greater than 0.1 mm.
[0050] Figure 1 The post-processing process of the silk fibroin block was further demonstrated. The silk fibroin block prepared by multi-layer bonding was placed in a constant temperature and humidity chamber at 85% RH for 2 hours, and then the silk fibroin block was compressed along the thickness direction at a pressure of 5 MPa to achieve densification and obtain a multi-layer bonded silk fibroin structural material.
[0051] Figure 2 a shows a silk fibroin block material after multi-layer composite but without densification treatment, indicating that the scheme of the present invention can be used to prepare large-sized (>5cm×5cm) silk fibroin sheets; Figure 2 b- Figure 2 c shows the test photos and test results of the interfacial adhesion energy of the bonded silk fibroin film, indicating that after dry hot roller pressing, its interfacial adhesion energy can reach up to 750 J m -2 .
[0052] Figure 3 a- Figure 3 c shows the cross-section photo of the densified silk fibroin sheet and the scanning electron micrographs of different regions. It can be seen that under the pressure of 5MPa, the silk fibroin sheet presents a macroscopic gradient structure, that is, a dense structure is formed at the edge, and the core layer maintains a porous structure. A 10U / ml protease E solution was prepared using 0.01M phosphate buffer solution, and the densified silk fibroin sheet was subjected to a degradation experiment at 37°C. Figure 3 d The results show that the porous core layer inside the silk fibroin board is completely degraded within one month, and the dense shell layer has no obvious degradation after six months, indicating that the densification pressure can also regulate the degradation process of the silk fibroin board.
[0053] In addition, the densification of silk fibroin blocks under 10MPa and 2MPa pressures was tested. The results showed that under 10MPa, the cross section showed a non-gradient uniform densification structure, and all pore phases were compressed and densified; under 2MPa pressure, a thinner dense shell layer could be prepared. The three-point bending method was used to test the ultimate bending strain, bending strength and bending modulus of the densified samples, and the simply supported beam impact test was used to test the impact strength. The fracture toughness was tested using the single-edge notched beam method.
[0054] Example 2
[0055] Step S1, firstly, 0.05 g of lithium chloride is added into 8.2 ml of formic acid for dissolution, and after the dissolution is completed, a lithium chloride-formic acid solution with a concentration of 0.5 wt % is obtained;
[0056] Step S2, taking 0.4 g of degummed silk and dissolving it in the above 7.8 ml of lithium chloride-formic acid solution, and placing it in an ultrasonic cleaning machine for oscillation for 1 hour, and obtaining a regenerated silk fibroin solution after oscillation;
[0057] Step S3, taking a clean PET (polyethylene terephthalate) substrate, using a four-sided preparation device with a thickness of 200 μm to scrape and coat the regenerated silk fibroin solution on the PET substrate, curing at room temperature to form a silk fibroin gel film, and drying the silk fibroin gel film;
[0058] Step S4, soaking the dried silk fibroin gel film in water for 10 minutes, and then placing the PET substrate with the silk fibroin gel film attached thereto in a vacuum freeze dryer for freeze drying, so that the silk fibroin gel film is frozen at a vacuum degree of 0.05 MPa and a cold trap temperature of -50°C, so that the surface of the silk fibroin gel film is spontaneously nucleated and frozen, and then freeze-dried in situ to obtain a porous silk fibroin film after freeze drying;
[0059] Step S5, peeling off the freeze-dried porous silk fibroin film from the PET substrate by mechanical peeling; the film thickness of the peeled porous silk fibroin film is about 60 μm, the pore size of the porous silk fibroin film is 200 nm ± 5 μm, and the amorphous structure component contained in the surface of the prepared porous silk fibroin film is 50% to 70% according to infrared spectroscopy analysis.
[0060] Step S6, bonding and compressing the peeled off multi-layer porous silk fibroin film in sequence by hot roller pressing, so as to obtain a multi-layer bonded silk fibroin structural material.
[0061] Step S6.1, firstly, hot rolling bonding two layers of porous silk fibroin films at a temperature of 100° C. to obtain a new porous silk fibroin film;
[0062] Step S6.2, repeating step S6.1 multiple times to achieve hot roller bonding of the multi-layer porous silk fibroin film to obtain a silk fibroin block, wherein the thickness of the prepared silk fibroin block is greater than 0.1 mm;
[0063] Step S6.3, then place the silk fibroin block that has been treated with hot roller bonding in a constant temperature and humidity chamber at a humidity of 85% RH for 2 hours, and finally compress the silk fibroin block along the thickness direction at a pressure of 5 MPa to achieve densification, and finally obtain a multi-layer bonded silk fibroin structural material.
[0064] After densification, the three-point bending method was used to test the ultimate bending strain, bending strength and bending modulus of the samples, and the simply supported beam impact test was used to test the impact strength. The single-edge notched beam method was used to test the fracture toughness.
[0065] Example 3
[0066] In addition to being able to be used to prepare pure silk fibroin multilayer composite plates, the present invention can also be used to prepare composite materials based on silk fibroin. This embodiment uses graphene oxide and silk fibroin composite as an example, but it is not intended to limit the present invention.
[0067] Step S1, firstly, 0.87 g of lithium bromide is added into 7.5 ml of formic acid for dissolution, and after the dissolution is completed, a lithium bromide-formic acid solution with a concentration of 8.7 wt % is obtained;
[0068] Step S2, taking 2.5g of degummed silk and dissolving it in the above 5.7ml of lithium bromide-formic acid solution, and placing it in an ultrasonic cleaning machine for oscillation for 1h, and obtaining a regenerated silk fibroin solution after oscillation; adding a graphene oxide aqueous solution with a concentration of 100mg / g to the above regenerated silk fibroin solution, controlling the mass ratio of graphene oxide to regenerated silk fibroin solution to be 20wt%, and mechanically stirring for 36h to fully disperse the graphene oxide in the regenerated silk fibroin solution;
[0069] Step S3, taking a clean PET (polyethylene terephthalate) substrate, coating the regenerated silk fibroin solution added with graphene oxide on the PET substrate using a four-sided preparation device with a thickness of 300 μm, curing at room temperature to form a silk fibroin gel film, and drying the silk fibroin gel film;
[0070] Step S4, soaking the dried silk fibroin gel film in water for 10 minutes, and then placing the PET substrate with the silk fibroin gel film attached thereto in a vacuum freeze dryer for freeze drying, so that the silk fibroin gel film is frozen at a vacuum degree of 0.05 MPa and a cold trap temperature of -50°C, so that the surface of the silk fibroin gel film is spontaneously nucleated and frozen, and then freeze-dried in situ to obtain a porous silk fibroin film after freeze drying;
[0071] Step S5, peeling the freeze-dried porous silk fibroin film from the PET substrate by mechanical peeling; the film thickness of the peeled porous silk fibroin film is about 90 μm, and the pore size of the porous silk fibroin film is 200 nm ± 5 um;
[0072] Step S6, bonding and compressing the peeled off multi-layer porous silk fibroin film in sequence by hot roller pressing, so as to obtain a multi-layer bonded silk fibroin structural material.
[0073] Step S6.1, firstly, hot roller bonding two layers of porous silk fibroin films at a temperature of 200° C. to obtain a new porous silk fibroin film; during the hot roller bonding process, the two layers of porous silk fibroin films are placed opposite to each other;
[0074] Step S6.2, repeating step S6.1 multiple times to achieve hot roller bonding of the multi-layer porous silk fibroin film to obtain a silk fibroin block; the overall thickness of the silk fibroin block is greater than 0.1 mm;
[0075] Step S6.3, then place the silk fibroin block that has been treated with hot roller bonding in a constant temperature and humidity chamber with a humidity of 85% RH for 2 hours, and finally compress the silk fibroin block along the thickness direction at a pressure of 5 MPa to finally obtain a multi-layer bonded silk fibroin structural material.
[0076] The densified samples were tested for ultimate bending strain, flexural strength and flexural modulus using the three-point bending method, and for impact strength using the simply supported beam impact test.
[0077] Comparative Example 1
[0078] Step S1, firstly, 0.48 g of calcium chloride is added into 7.8 ml of formic acid to dissolve, and after the dissolution is completed, a calcium chloride-formic acid solution with a concentration of 4.8 wt % is obtained;
[0079] Step S2, taking 1.3 g of degummed silk and dissolving it in the above 6.8 ml of calcium chloride-formic acid solution, and placing it in an ultrasonic cleaning machine for oscillation for 1 hour, and obtaining a regenerated silk fibroin solution after oscillation;
[0080] Step S3, pouring the regenerated silk fibroin solution into a culture dish and standing for >12 hours to allow the formic acid to fully volatilize. Treating the obtained sample in circulating water to prepare a silk fibroin gel block. Vacuum drying the obtained gel block under controlled compression conditions in the thickness direction can prepare a silk fibroin board without a hierarchical structure and a porous structure.
[0081] The three-point bending method was used to test the ultimate bending strain, bending strength and bending modulus, the simply supported beam impact test was used to test the impact strength, and the single-edge notched beam method was used to test the fracture toughness.
[0082] Comparative Example 2
[0083] Since the silk fibroin structural material of the present invention has a hierarchical structure with micrometer and nanometer interfaces, its structural characteristics are similar to the structure of natural shell nacre. As a comparison, the nacre material of Unionidae nacre was used for mechanical testing.
[0084] The three-point bending method was used to test the ultimate bending strain, bending strength and bending modulus, the simply supported beam impact test was used to test the impact strength, and the single-edge notched beam method was used to test the fracture toughness.
[0085] For the convenience of representation in the diagram, the densified sample prepared in Example 1 was named HAS400, the densified sample prepared in Example 2 was named HAS200, the densified sample prepared in Example 3 was named Silk-GO, the sample prepared in Comparative Example 1 was named Silk plate, and the sample prepared in Comparative Example 2 was named Natural nacre.
[0086] Table 1 shows the three-point bending and simply supported beam impact test results of the samples of Examples 1 to 3 and Comparative Examples 1 to 2. It can be seen that the prepared densified silk block also has excellent mechanical properties. Thanks to its hierarchical structure characteristics of micrometer and nanometer scale coordination, its bending strength can reach 130MPa, bending modulus can reach 5.7GPa, and impact strength can reach 10kJm -2 Controlling the overall thickness of the monolayer is also beneficial to enhancing the overall performance of the bulk material after densification.
[0087] Table 1 Three-point bending and simply supported beam impact test results
[0088]
[0089] Figure 4 The single-edge notch beam test results of the samples of Example 1-Example 2 and Comparative Example 1-Comparative Example 2 are further shown. The samples are cut with a diamond cutting wire of 100 μm in diameter to obtain a single-edge notch. The obtained structure is as follows: Figure 4 As shown in a. Figure 4 b shows the crack initiation toughness (K Ic ) and crack growth toughness (K Jc ). It can be seen that the multi-layer composite silk protein structure material K Ic The value is 1~1.3MPa m 1 / 2 , lower than the K of natural nacre structure Ic Value (2.32±0.67MPa m 1 / 2 ). From crack initiation to the end of stable crack extension, the maximum fracture toughness K of the multilayer silk structure material JcIncreased by 4-7 times. The final K Jc It exceeds the natural pearl and pure silk bulk materials, indicating the effectiveness of the designed layered structure. Figure 4 c) Evaluate the toughening mechanism. Compared with pure silk fibroin blocks, the excellent mechanical properties of multilayer composite silk fibroin structural materials are due to their enhanced fracture resistance, which is similar to the structure of natural pearl layers. Its maximum fracture toughness can reach 7.70±0.39MPa m 1 / 2 , exceeding the 3.56±2.22MPa m of natural pearl oyster 1 / 2 .
[0090] In addition to preparing a planar silk block, the present invention also provides an embodiment of processing a silk board into a three-dimensional plate shape. Figure 5 As shown, according to the required structural characteristics, a shaping mold is designed and 3D printed. After the multilayer composite silk structure prepared in Example 1 is softened or densified, the silk structure is placed in a 3D printed mold, and bolts are used to provide clamping force, and then vacuum drying is performed at 60°C to prepare a three-dimensional structure of silk protein.
[0091] Figure 6 a- Figure 6 d shows a photo of the sample after the multilayer silk protein block was shaped using a hemispherical mold, and the mechanical curve of the three-dimensional structure's resistance to compression was tested using radial compression. Figure 6 c is a cross-sectional scanning electron micrograph of the sample after fracture. It can be seen that there are crack bending and extension interfaces at both the micrometer and nanometer scales. Figure 6 d is the mechanical compression curve. The compressive force that can be sustained can reach ~80N. There is an energy absorption mechanism based on crack extension and interface failure in the fracture process.
[0092] Comparative Example 3
[0093] For comparison, the dense silk fibroin block prepared in Comparative Example 1 was also placed in a hemispherical 3D printing mold, with bolts used to provide clamping force, and then vacuum dried at 60°C to prepare a three-dimensional structure of a dense silk fibroin block. Figure 7 a shows a digital photo of the silk block after shaping. Figure 7 b- Figure 7 c shows the three-dimensional structure compression test process and fracture cross-section photo. It can be seen that the crack extension interface is smooth. Figure 7 In d, its fracture curve shows that the compression force it can withstand is ~40N.
[0094] Comparative Example 4
[0095] In order to facilitate understanding of the bionic characteristics of the multi-layer composite silk protein structure of the present invention, the compression failure curve of the natural shell three-dimensional structure is also shown as a comparison. Figure 8 As shown, the compressive force that natural shells can withstand is ~40N, which is similar to the three-dimensional structure of silk fibroin. The fracture process of natural shells involves an energy absorption mechanism based on crack propagation and interface failure.
[0096] Personnel in the technical field can easily make various changes and modifications based on the text description, drawings and claims provided by the present invention without departing from the concept and scope of the present invention defined by the claims. Any modification or equivalent change made to the above embodiments based on the technical concept and essence of the present invention shall fall within the scope of protection defined by the claims of the present invention.
Claims
1. A multilayer bonding method for silk fibroin structural materials, characterized in that: The following steps are involved: Step S1, firstly, adding a halide salt into formic acid to dissolve it, and after the dissolution is completed, a halide salt-formic acid solution is obtained; Step S2, taking degummed silk and dissolving it in the halide-formic acid solution, and placing it in an ultrasonic cleaning machine for oscillation to obtain a regenerated silk fibroin solution; Step S3, taking a clean PET substrate, coating the regenerated silk fibroin solution on the PET substrate using a four-sided preparation device, and curing at room temperature to form a silk fibroin gel film; Step S4, soaking the dried silk fibroin gel film in water for a preset time, and then placing the PET substrate with the silk fibroin gel film attached thereto into a vacuum freeze dryer for freeze drying to obtain a porous silk fibroin film; Step S5, peeling off the porous silk fibroin film obtained after freeze-drying from the PET substrate, and sequentially performing hot roller bonding and compression on the peeled layers of porous silk fibroin film to obtain a multi-layer bonded silk fibroin structural material.
2. A multilayer bonding method for a silk fibroin structural material according to claim 1, characterized in that: The mass concentration of the halide salt-formic acid solution obtained in step S1 is 0.5-8.7wt%; the halide salt in step S1 includes one of lithium chloride, lithium bromide and calcium chloride.
3. The multilayer bonding method of a silk fibroin structural material according to claim 1, characterized in that: In the step S2, the mass ratio of the degummed silk in the halide-formic acid solution is 8-15 wt %.
4. The multilayer bonding method of a silk fibroin structural material according to claim 1, characterized in that: In step S4, the specific steps of freeze-drying the silk fibroin gel film are as follows: the silk fibroin gel film is frozen at a vacuum degree of 0.05 to 0.1 MPa and a cold trap temperature of -60 to -50°C to allow spontaneous nucleation on the surface of the silk fibroin gel film, and then freeze-dried in situ to obtain a porous silk fibroin film after freeze-drying.
5. The multilayer bonding method of a silk fibroin structural material according to claim 1, characterized in that: In the step S4, the film thickness of the porous silk fibroin film is 60 μm to 120 μm, and the pore size of the porous silk fibroin film is 200 nm to 5 um.
6. The multilayer bonding method of a silk fibroin structural material according to claim 1, characterized in that: In the step S5, the multi-layer porous silk fibroin film is hot-rolled bonded at a temperature of 100°C to 200°C, and then the porous silk fibroin film treated with hot-rolling bonding is placed in a constant temperature and humidity chamber with a humidity of 80% to 85% RH for 2 to 3 hours, and finally the porous silk fibroin film is compressed along the thickness direction at a pressure of 5MPa to 6MPa to finally obtain a multi-layer bonded silk fibroin structural material.
7. The multilayer bonding method of a silk fibroin structural material according to claim 1, characterized in that: In the step S5, the thickness of the finally obtained multi-layer bonded silk fibroin structural material is greater than 0.1 mm.
8. The multilayer bonding method of a silk fibroin structural material according to claim 1, characterized in that: The regenerated silk fibroin solution is added with a graphene oxide aqueous solution with a concentration of 100 mg / g to 200 mg / g.
9. A silk fibroin structural material, characterized in that: The silk fibroin structural material is prepared by the preparation method described in any one of claims 1-8.
10. An application of the silk fibroin structural material prepared by the method according to any one of claims 1 to 8, characterized in that: The application of the silk fibroin structural material in preparing scaffold materials.